2020
DOI: 10.3390/nano10112126
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Evaluation of Nanostructured Silica Orally Administered to Rats: Influence on Immune System Function

Abstract: The experimental data on the oral toxicity of nanostructured amorphous silica (SiO2), widely used in food supplements, pharmaceuticals, and cosmetics, in terms of its in vivo effect on the immune system, are contradictory. Therefore, this study aimed to assess the rat’s immune function after SiO2 oral administration. In the first experiment, SiO2 was daily orally administered to Wistar rats for 92 days in doses of 0.1, 1.0, 10, and 100 mg/kg of body weight (bw). In the second 28-day experiment, SiO2 in a dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In addition to effects on the liver, oral exposure to SAS has been associated with other adverse effects and health syndromes. These include local effects on the intestine, inflammatory bowel diseases, effects on the immune system, and effects associated with microbiome alterations (Gmoshinski et al 2020;Lamas, Martins Breyner, and Houdeau 2020;Siemer et al 2018;Winkler, Suter, and Naegeli 2016;Yan et al 2020), and effects on kidney (Boudard et al 2019). In the current paper, we focused mainly on hepatotoxic effects, as multiple studies indicated liver as critical target organ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to effects on the liver, oral exposure to SAS has been associated with other adverse effects and health syndromes. These include local effects on the intestine, inflammatory bowel diseases, effects on the immune system, and effects associated with microbiome alterations (Gmoshinski et al 2020;Lamas, Martins Breyner, and Houdeau 2020;Siemer et al 2018;Winkler, Suter, and Naegeli 2016;Yan et al 2020), and effects on kidney (Boudard et al 2019). In the current paper, we focused mainly on hepatotoxic effects, as multiple studies indicated liver as critical target organ.…”
Section: Discussionmentioning
confidence: 99%
“…Recent some research showed the potential toxicity of SAS in terms of inflammation of the intestinal wall and neurotoxicity [ 15 , 16 , 17 , 18 ]. Contradictory in vivo toxicity results were also reported, showing the low oral toxicity of SAS [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 94%
“…Most of the available data concern ASNP-induced changes in the mechanical mechanisms of the barrier. In a study aimed to assess changes in rat immune system after ASNP oral administration (daily, in doses ranging from 0.1 to 100 mg/kg of body weight for 92 days), Gmoshinski et al found no modification of intestinal permeability to protein macromolecules (ovalbumin) [ 45 ], suggesting a relative insensitivity of the intestinal barrier to ASNP. This study was consistent with the assumption of low toxicity of ASNP on intestinal structure and function, although the ASNP characterization was incomplete, thus preventing a proper comparison with other studies.…”
Section: Local Intestinal Effects: Genotoxicity Cytotoxicity Inflamma...mentioning
confidence: 99%